FAKTOR YANG MEMPENGARUHI NIAT MENGGUNAKAN APLIKASI BELANJA SELULER DI KALANGAN GENERASI X: PENDEKATAN DENGAN APLIKASI UTAUT - Rafnelly Rafki; Rinda Lestari; Nofriadi Nofriadi; Yolanda Oktarina; Nova Mustika (Pusat Riset dan Inovasi Nasional, 2023)
Currently, the development of digital technology has an influence on all human lives, including shopping problems, namely online shopping applications. A lot of research has been done to study it, but there hasn't been much study of the factors that influence the intention to use online apps in generation X. So the purpose of this study is to study the factors that influence the intention to use mobile shopping applications among generation x, using the UTAUT application approach The method used is the UTAUT Model (Unified Theory of Acceptance and Use of Technology), the Integrated Theory of Acceptance and Use of Technology. The UTAUT model is used to be applied to the context of mobile shopping application use among Generation X. This research is a survey research using questionnaires as a data collection instrument. The sample is the Generation X Group who use smartphones and often do online shopping transactions. What influences a person's intention in the use of technology, it turns out to be between: 1) perception of ease of use, 2). perception of usefulness, 3). subjective norms, and 4). perception of quality. What influences a person's intention in the use of technology, it turns out to be between: 1) perception of ease of use, 2). perception of usefulness, 3). security, and 4). l. It can be concluded that the most significant factors in influencing the intention to use mobile shopping apps among Generation X are in terms of ease of use. This can be the basis for designing more effective marketing and promotion strategies for mobile shopping application service providers, and can help increase user satisfaction and strengthen consumer loyalty.